Screening and characterization estrogen receptor ligands from Arnebia euchroma (Royle) Johnst. via affinity ultrafiltration LC-MS and molecular docking - Zhu, Lian; Ma, Sheng-jun; Liu, Ming-juan; Li, Kai-lin; E, Shuai; Wang, Zi-ming; Li, Sha-ni; Zhang, Sheng-lan; Cai, Wei (Frontiers in Plant Science, 2022)
Arnebiae Radix (dried root of Arnebia euchroma (Royle) Johnst.) is a traditional Chinese medicine (TCM) used to treat macular eruptions, measles, sore throat, carbuncles, burns, skin ulcers, and inflammations. The Arnebiae Radix extract can exert anti-breast cancer effects through various mechanisms of action. This study aimed to rapidly screen potential estrogen receptor (estrogen receptor α and estrogen receptor β) ligands from the Arnebiae Radix extract. In this study, an analytical method based on affinity ultrafiltration coupled with UHPLC-Q-Exactive Orbitrap mass spectrometry was established for rapidly screening and identifying estrogen receptor ligands. Then, bindings of the components to the active site of estrogen receptor (estrogen receptor α and estrogen receptor β) were investigated via molecular docking. Moreover, surface plasmon resonance (SPR) experiments with six compounds were performed to verify the affinity. As a result, a total of 21 ligands were screened from Arnebiae Radix using affinity ultrafiltration. Among them, 14 and 10 compounds from Arnebiae Radix showed affinity with estrogen receptor α and estrogen receptor β, respectively. All of those ligands could have a good affinity for the multiple amino acid residues of the estrogen receptor based on molecular docking. In addition, six compounds display the great affinity by SPR. The method established in the study could be used to rapidly screen estrogen receptor ligands in Traditional Chinese medicine. The results demonstrated that the affinity ultrafiltration–UHPLC-Q-Exactive Orbitrap mass spectrometry method not only aids in the interpretation of the potential bioactive components and possible mechanisms of action of Arnebiae Radix but also provides a further effective basis for the quality control of this valuable herb medicine.